New records of snakes (Squamata: Serpentes) from Huu Lien nature reserve, Lang Son province - Thuyen, Nguyen Thi; Son, Nguyen Lan Hung; Dung, Le Trung; Tao, Nguyen Thien (Academia Journal of Biology, 2018)
Based on a new reptile collection from Huu Lien Nature Reserve, Lang Son Province we added six new records of snakes found in the nature reserve, viz., Ahaetulla prasina, Boiga kraepelini, Chrysopelea ornata, Lycodon fasciatus, Oligodon chinensis, and Sinomicrurus macclellandi. Our findings increased the species number of snakes to 21 in Huu Lien Nature Reserve and 49 in Lang Son Province.